Revised and Republished Ordinances of The City of Joplin, Missouri 201, § 76 (1903) - (:unkn) unknown (My University, 1903)
Ordinances that prohibit carrying concealed weapons, bringing weapons to certain places, and firing weapons, Ch. 23, Art. 1, Ord. No. 2019, § 76: Any person who shall, in this city, without sufficient or reasonable cause, discharge any revolver, pistol, gun or other fire-arm shall be deemed guilty of a misdemeanor, and be fined in a sum of not less than five dollars, nor more than fifty dollars for each shot discharged."
Keywords: DISCHARGE